THE IMPLEMENTATION OF PROJECT-BASED LEARNING MINI-RESEARCH TASKS ON STUDENTS' LEARNING OUTCOMES DURING THE PANDEMIC - Listiani, Tanti; Dirgantoro, Kurnia (Universitas Pelita Harapan, 2023)
Statistics for Research Education is an important course for students in the Faculty of Education. Serious problems are experienced by students learning statistics, one of them is because the learning outcomes are not optimal. To overcome this problem, a lecturer can provide mini-research tasks. Mini-research is one form of assignment from project-based learning. This research was descriptive qualitative research. The subjects in this study were students from Cohort 2019 who took Educational Research Statistics courses. Learning activities and mini-research assignments are handled fully online. By giving students a mini-research assignment, students can be encouraged to learn statistical theories and concepts. Through mini-research tasks, students can increasingly see the big picture and interrelationships between topics in this course. The positive responses can be seen from students’ reflections and results of the review given to the paper. The use of project-based learning with a mini-research task is an interesting idea and suitable for students. In addition to better student learning outcomes, students also become more conscious of the problems around them. Prospective teachers can learn to make research an upcoming provision when they enter the field of teaching.